A comprehensive review of ethnomedicinal approaches, phytochemical analysis, and pharmacological potential of Vitex trifolia L. - Javad Mottaghipisheh; Marzie Kamali; Amir Hossein Doustimotlagh; Amir Hossein Doustimotlagh; Mohammad Hossein Nowroozzadeh; Fatemeh Rasekh; Mohammad Hashem Hashempur; Aida Iraji (Frontiers Media S.A., 2024)
Plants, renowned for their rich reservoir of metabolites, play a pivotal role in addressing health-related issues. The Verbenaceae family stands out, showcasing immense potential in preventing and treating chronic diseases. Vitex trifolia L. (V. trifolia), a shrub with a rich history in traditional medicine, particularly in Eastern Asia, has garnered attention for its diverse therapeutic applications. This comprehensive review aims to bridge traditional knowledge and contemporary insights by investigating ethnopharmacology, phytochemistry, and pharmacological effects of V. trifolia. The keyword "V. trifolia" and its synonyms were searched within the main scientific databases including PubMed, Web of Science, ScienceDirect, Google Scholar, and Baidu Scholar (from 1974 to 2022, last search: 21.10.2023). Phytochemical analyses reveal a spectrum of secondary metabolites in V. trifolia, including terpenoids, flavonoids, lignans, phytosterols, anthraquinones, and fatty acids. Notably, terpenoids and flavonoids emerge as the main bioactive metabolites. Pharmacological studies validate its therapeutic potential, demonstrating significant antioxidant, anti-inflammatory, hepatoprotective, anticancer, anti-amnesic, antimicrobial, antiviral, anti-malaria, antispasmodic activities, and reported insecticidal effects. Despite existing literature exploring pharmacological attributes and secondary metabolites of related species, a conspicuous gap exists, specifically focusing on the pharmacological activities and novel methods of purification of pure metabolites from V. trifolia. This review aimed to fill this gap by delving into traditional medicinal applications, exploring secondary metabolites comprehensively, and providing an in-depth analysis of pharmacological effects of pure metabolites. Combining traditional uses with contemporary pharmacological insights, this article sought to serve as a crucial reference for future research and practical application of V. trifolia. This approach contributes substantially to understanding the plant, fostering scientific inquiry, and facilitating its broader application in healthcare.